Типи та причини раритетності на прикладі видів рослин Українських Карпат - Кобів, Ю.Й. (Український ботанічний журнал, 2010)
Приведен обзор различных аспектов проблемы раритетности применительно к видам сосудистых растений Украинских Карпат. Рассмотрены формы (по D.S. Rabinowitz, 1981) и типы редкости видов, обусловленные площадью их распространения, экологической приуроченностью и численностью популяций, а также естественными и антропогенными причинами. Указано на угрозу вымирания некоторых редких видов в заброшенных послелесных луговых сообществах вследствие их массового зарастания кустарниковой и древесной растительностью. Проанализирована взаимосвязь между редкостью видов и их биологическими особенностями. A review of various aspects of the problem of rarity applied to rare species of vascular plants in the Ukrainian Carpathians is presented. Forms (according to D.S. Rabinowitz, 1981) and types of species rarity referring to the area of their distribution, ecological requirements and population numbers, as well as natural and anthropogenic causes, are discussed. The threat of extinction of some rare species in abandoned semi-natural post-forest grassland communities due to their vast overgrowth with shrubby and woody vegetation is pointed out. Relationship between the species rarity and their biological characteristics is analyzed.